DLP 3D printing of alumina catalyst architectures: Design, kinetics and modeling of structure effects on catalyst performance - Mastroianni, Luca; Jesus Medina Ferrer, Ananias De; De Domenico, Anna Maria; Eränen, Kari; Serio, Martino Di; Murzin, Dmitry; Russo, Vincenzo; Salmi, Tapio (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
[Display omitted] •Periodic alumina catalyst structures were designed and printed with DLP printing technology.•The catalyst performance was demonstrated in the ethanol dehydration to diethyl ether.•A mathematical model, including relevant geometrical features, was derived and solved numerically.•The model gave a successful description of the experimental data. The impact of the 3D structural design on the catalytic performance was investigated in this work. Four catalyst architectures (squared honeycomb, Schwartz P, face centered cubic and gyroid), made of alumina, were designed and printed with the Digital Light Processing (DLP) printing technology. The obtained shaped catalysts were loaded in a tubular reactor and their activities were evaluated in continuous ethanol dehydration to diethyl ether. The kinetic experiments revealed that both the conversion per unit of the reactor volume and the specific activity were highly affected by the selected design of the catalyst geometry. An advanced 1-D heterogeneous mathematical model employing geometrical features of the catalyst structures was proposed to describe the experimental data. The model included local variations of contact perimeters and cross-section areas to describe the periodic architectures. The assumption of plug flow pattern in the catalyst channels was revealed to be inadequate in predicting the structure effects, thus axial dispersion effects were included to obtain a successful and statistically significant description of the experimental observations. The proposed approach forms a solid basis to describe chemical processes operated with 3D printed catalyst structures.